Modelo para el análisis técnico-económico de la factibilidad de microcentrales eólicas para generación distribuida - Minango Paredes, Manuel Antonio (2014)
The present thesis project develops criteria for the calculation of the technical-economic feasibility of a wind project at the level of residential distributed generation; through a computational model that also allows the calculation of the sensitivity on factors such as: the initial investment, the wind speed, the interest rate and the prices for purchase and sale of energy. Theoretical-documentary information is presented about: smart grids, types of existing power stations, distributed generation and wind power stations. On this basis, it will establish the equations and values that relate to the behavior and functions of wind turbines at the level of residential distributed generation. In addition it contains the results of the sensitivity analyzes in several possible scenarios that could face a wind project at the level of distributed generation on the Ecuadorian reality. It also presents conclusions and recommendations. Index of Terms.- Wind Turbines, Power Stations, Wind Power Stations, Residential Demand, Distributed Generation, Micro Power Stations, Smart Grids